1993
DOI: 10.1007/bf00204041
|View full text |Cite
|
Sign up to set email alerts
|

Source of metals and age constraints for epigenetic gold deposits in the Skellefte and Pohjanmaa districts, central part of the Fennoscandian Shield

Abstract: Abstract. The lead isotopic compositions of galena in Early Proterozoic gold deposits have been determined for three districts in northern Sweden and central Finland. The deposits are hosted by a variety of ~ 1870-1890 Ma Svecofennian host rocks including the volcanosedimentary succession within the Skellefte District island arc in Sweden as well as I-type tonalites at J6rn (Sweden) and Pohjanmaa (Finland). The deposits are epigenetic in relation to these Svecofennian rocks and are part of a goldbearing metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The age of this intrusive-hosted deposit is constrained to c. 1886 Ma (U-Pb dating of the related porphyritic intrusive; Weihed and Sch6berg 1991). This adds further support to the importance of early plutonic processes and linked gold mineralization (compare Sundblad et al 1993) and the hypothesis that surface-derived waters were important for the concentration of gold.…”
Section: Fluid Evolution and Gold Depositionsupporting
confidence: 70%
“…The age of this intrusive-hosted deposit is constrained to c. 1886 Ma (U-Pb dating of the related porphyritic intrusive; Weihed and Sch6berg 1991). This adds further support to the importance of early plutonic processes and linked gold mineralization (compare Sundblad et al 1993) and the hypothesis that surface-derived waters were important for the concentration of gold.…”
Section: Fluid Evolution and Gold Depositionsupporting
confidence: 70%
“…Groves et al [65] suggested that the presence of W-Sn deposits in the magmatic province and a continental tectonic setting well inboard of convergent plate boundaries as diagnostic for intrusion-related type of deposits. There are no W-Sn deposits in the Åkerberg area, although such mineralizations occur in the so called -Au line‖ west of the Skellefte district where some potential intrusion-related deposits occur [14,24]. However, Åkerberg is tentatively situated in a back-arc region [34] which appears to be consistent with a typical tectonic setting for the intrusion-related group of deposits.…”
Section: Classifying the åKerberg Gold Deposit: An Intrusion-related mentioning
confidence: 68%
“…2. Additional data are from Vaasjoki and Vivallo (1990) and Sundblad et al (1993). The bulk of the lead is fixed in galena and sulphosalts and unless otherwise stated, the following discussion refers to such data.…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the need to characterize the individual source components that have contributed to the a The analyses have been performed at Helsinki (G-numbers), at Geospec, Canada (Sk-numbers) and at LIG, Stockholm (LIG-numbers). Helsinki data have been published by Vaasjoki and Vivallo (1990) and Vindelgransele data by Sundblad et al (1993) b Unless otherwise stated the mineral analyzed is galena; sp, sphalerite; py, pyrite; su, sulphosalt c Model ages and #-values (present-day 23aU/2~ have been calculated according to Stacey and Kramers (1975) analyzed lead mixtures and to derive a model for the lead isotopic evolution that is consistent with the local geology.…”
Section: Resultsmentioning
confidence: 99%